2017
DOI: 10.1111/ajt.14097
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Responses to Collagen Type V, kα1-Tubulin, and Vimentin Are Present Early in Human Development and Persist Throughout Life

Abstract: Th17-dependent autoimmune responses can develop after heart or lung transplantation, and are associated with fibro-obliterative forms of chronic rejection. However, the specific self-antigens involved are typically different from those associated with autoimmune disease. To investigate the basis of these responses, we questioned whether removal of Tregs or blockade of function reveals a similar auto-antigen bias. We found that Th17 cells specific for collagen type V (Col V), kα-1-tubulin, and vimentin were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…We have shown that the natural T h 17 response to ColV can be induced by the 160-aa-long ColV a1 fragments but not the 15mer peptides of ColV (9). Additionally, in this study, we have demonstrated that sLAIR1/Fc binds the ColV fragment but not the peptide (Fig.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…We have shown that the natural T h 17 response to ColV can be induced by the 160-aa-long ColV a1 fragments but not the 15mer peptides of ColV (9). Additionally, in this study, we have demonstrated that sLAIR1/Fc binds the ColV fragment but not the peptide (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…We first sought to determine whether B6 mice (background of the LAIR1 2/2 mice) had pre-existing responses to ColV, similar to those reported for the CBA mice (9). Using the trans-vivo bioassay system we demonstrated that whole spleen cells from naive wild-type (WT) B6 mice did not respond to ColV (Fig.…”
Section: Pre-existing T H 17 Responses To Colv Are Abolished By Genetmentioning
confidence: 91%
See 2 more Smart Citations
“…Using the trans vivo delayed-type hypersensitivity assay, we show that NeoThy T cells mount a collagen V-specific effector response to co-injected antigen in the presence of anti-transforming growth factor β neutralizing antibody. This demonstrates the utility of the NeoThy for study of innate-like Th17 cell function in the context of iPSC immunogenicity ( Sullivan et al., 2017 ). Last, NeoThy mice challenged with a B6 skin graft mounted rejection responses characterized by the two metrics of (1) hCD3 + T cell infiltration and (2) visible graft loss over time, similar to fetal tissue controls ( Figures 3 D and 3E).…”
Section: Resultsmentioning
confidence: 83%